PRACTICAL MODEL OF INDIGENOUS CO-CREATION FOR THE SUSTAINABILITY OF INDONESIAN WOVEN SONGKET - Retno Kusumastuti (Hasanuddin Economics and Business Review, 2018)
Innovation is the main key to the sustainability of all industries. Fashion industry with traditional woven as its basic material is one of complex industries for its association with social environment in all cultural values, market taste, chain value, life cycle products and even government policy. This focus will likely be important as indigenous characteristic in the traditional woven becomes the competitive advantage of a region. The outcome of this study showed that traditional woven co-creation in design need an involvement of social actors in the social learning process. Indigenous co-creation of traditional woven is a social innovation learning activities that needs adequate involvement of actors and context. The purpose of this study is to analyze the challenges and constraints for the sustainability of Indonesian woven songket and to develop a practical co-creation model in attempt to cope with various constraints to generate recommendation for decision makers at local goverment level. This study used qualitative approach. The primary and secondary data to answer the research questions were collected through in-depth interview and focus group discussion.Â